Mongolia Agricultural Sector Risk Assessment - World Bank Group (World Bank, Washington, DC, 2015)
The magnitude of risks facing Mongolian agriculture has made the sector’s development extraordinarily volatile over the last 25 years as it underwent decollectivization. Livestock in particular has seen rapid and largely unsustainable rates of growth in terms of numbers of animals and herders, and in so doing has become acutely vulnerable to the severe winter weather events known as dzuds. Periodic droughts and other production risks have also affected the country’s much smaller crop agriculture, much of which is geared for the production of feeds. And price volatility poses serious systemic risks which affect large proportions of the rural population. This study was undertaken to assess the systemic risks facing Mongolian agriculture and to identify gaps in current risk management practices within the sector.